Relationship between traditional and ballistic squat exercise with vertical jumping and maximal sprinting - Requena, B.; Garcia, I.; Requena, F. de Villarreal, E. S. -S.; Gronin, J. B. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to quantify the magnitude of the relationship between vertical jumping and maximal sprinting at different distances with performance in the traditional and ballistic concentric squat exercise in well-trained sprinters. Twenty-one men performed 2 types of barbell squats (ballistic and traditional) across different loads with the aim of determining the maximal peak and average power outputs and 1 repetition maximum (1RM) values. Moreover, vertical jumping (countermovement jump test [CMJ]) and maximal sprints over 10, 20, 30, 40, 60, and 80 m were also assessed. In respect to 1RM in traditional squat, (a) no significant correlation was found with CMJ performance; (b) positive strong relationships (p < 0.01) were obtained with all the power measures obtained during both ballistic and traditional squat exercises (r = 0.53-0.90); (c) negative significant correlations (r = -0.49 to -0.59, p < 0.05) were found with sprint times in all the sprint distances measured when squat strength was expressed as a relative value; however, in the absolute mode, no significant relationships were observed with 10- and 20-m sprint times. No significant relationship was found between 10-m sprint time and relative or absolute power outputs using either ballistic or traditional squat exercises. Sprint time at 20 m was only related to ballistic and traditional squat performance when power values were expressed in relative terms. Moderate significant correlations (r = -0.39 to -0.56, p < 0.05) were observed between sprint times at 30 and 40 m and the absolute/relative power measures attained in both ballistic and traditional squat exercises. Sprint times at 60 and 80 m were mainly related to ballistic squat power outputs. Although correlations can only give insights into associations and not into cause and effect, from this investigation, it can be seen that traditional squat strength has little in common with CMJ performance and that relative 1RM and power outputs for both squat exercises are statistically correlated to most sprint distances underlying the importance of strength and power to sprinting.